2020
DOI: 10.1088/1742-6596/1697/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and fibrillar structure collagen analysis by FTIR spectroscopy

Abstract: The main component of connective tissue and human organs — collagen protein is widely used in tissue engineering, regenerative medicine and cosmetology. The new methods search for assessing the structural and qualitative characteristics of collagen is currently an urgent area. This research is devoted to analyze by FTIR spectroscopy the various structural forms of collagen during the transition from molecular to fibrillar form and also collagen fibrils destruction. It was shown that during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…We observed the presence of amide III at 1340 cm −1 , confirming that the intact triple-helical structure of collagen was well maintained [27,30,31]. Previous analyses have reported that peptide bonds in the collagen structure can be damaged by UV exposure [31,32]; however, we did not find changes or absences in the elemental analysis of the composition of the collagen peptide, suggesting that UV irradiation did not impair collagen crosslinking.…”
Section: Resultssupporting
confidence: 77%
“…We observed the presence of amide III at 1340 cm −1 , confirming that the intact triple-helical structure of collagen was well maintained [27,30,31]. Previous analyses have reported that peptide bonds in the collagen structure can be damaged by UV exposure [31,32]; however, we did not find changes or absences in the elemental analysis of the composition of the collagen peptide, suggesting that UV irradiation did not impair collagen crosslinking.…”
Section: Resultssupporting
confidence: 77%
“…According to previously published data, there is an intensity increase at the amide III peak (1.242 cm −1 ) when collagen transitions from monomeric solution to fibrillar structures [ 35 ]. Earlier, we also confirmed the possibility of using FTIR spectroscopy to analyze the transition of collagen from molecular to fibrillar form [ 36 ]. This peak (1.242 cm −1 ) corresponds to an N-H bending mode that is attributed to the proline side chains in fibrillar collagen [ 37 ].…”
Section: Resultssupporting
confidence: 73%
“…Collagen displays bands at 1647, 1547, and 1240 cm −1 , which are characteristic of the amide I, II, and III bands of collagen. The amide I absorption arises predominantly from protein amide C=O stretching vibrations [ 36 ]. The amide II absorption is made up of amide N–H bending vibrations and C–N stretching vibrations.…”
Section: Resultsmentioning
confidence: 99%